Trade and Ethnicity: Business Ethics and the Glory of Maritime Trade of The Makassar’s Wajorese in the 18th Century - Bambang Sulistyo (Journal of Maritime Studies and National Integration, 2020)
This article aims to trace the role of the book Amanna Gappa, also known as Ade Alopping-loping Bicarana Pabalue, as a set of business ethics practiced by the Wajo ethnic group in the city of Makassar in the 18th century. The Wajo people of Makassar at that time were one of the tribes that lost the war between the Goa-Tallo Sultanate and the alliance of the Sultanate of Bone and the Dutch trading company VOC (Vereenigde Oost-Indische Compagnie) in the 1660s. The Wajo people were famous as great traders in Southeast Asia and their communities are scattered across the Indonesian archipelago. This article argues that one of the factors for their success in maritime trade is their ability to create business rules and ethics in maritime navigation and trade. Some scholars refer to this set of rules as the law of navigation or the law of commerce. However, this research seeks to explain that this set of rules was a set of maritime business ethics practiced by the Wajorese as traders and sailors. The Wajo people were not rulers of a sovereign state and were unlikely to have been able to enforce their business ethics as a law.